1980
DOI: 10.1111/j.1432-1033.1980.tb04832.x
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of the Core Region of Yeast Mannoproteins. Formation of a Glucosylated Dolichol-Bound Oligosaccharide Precursor, Its Transfer to Protein and Subsequent Modification

Abstract: A new membrane preparation from Saccharomyces cerevisiae was developed, which effectively catalyzes the synthesis of large oligosaccharide-lipids from GDP-Man and UDP-Glc allowing a detailed study of their formation and size.The oligosaccharide from an incubation with GDP-Man could be separated by gel filtration chromatography into several species consisting of two N-acetylglucosamine (GlcNAc) residues at the reducing end and differing by one mannose unit; the major compound formed has the composition (Man)g(G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 117 publications
(35 citation statements)
references
References 49 publications
(11 reference statements)
1
34
0
Order By: Relevance
“…It has been reported that in animal tissues (2,3), yeasts (4)(5)(6), and probably also in insects (7) and plants (8), the oligosaccharide transferred from the lipid derivative to proteins is composed of two N-acetylglucosamine, nine mannose, and three glucose residues. A report by Lehle suggests that in yeast the oligosaccharides containing two or three glucose residues are equally transferred to protein (9). However, no evidence was presented indicating that the oligosaccharides used in the assay had the same specific activity.…”
mentioning
confidence: 94%
“…It has been reported that in animal tissues (2,3), yeasts (4)(5)(6), and probably also in insects (7) and plants (8), the oligosaccharide transferred from the lipid derivative to proteins is composed of two N-acetylglucosamine, nine mannose, and three glucose residues. A report by Lehle suggests that in yeast the oligosaccharides containing two or three glucose residues are equally transferred to protein (9). However, no evidence was presented indicating that the oligosaccharides used in the assay had the same specific activity.…”
mentioning
confidence: 94%
“…Besides plants, UDP-glucose:sterol glucosyltransferase activity was determined by in vitro enzyme assays in Saccharomyces cerevisiae (45)(46)(47)(48), Candida bogoriensis (49), other fungi (50), and Physarum polycephalum (51,11). Although the lipid composition of S. cerevisiae was studied in detail during the last decades, there are only rare reports on the actual isolation of sterol glucoside (SG) 1 from this yeast (8,9).…”
mentioning
confidence: 99%
“…In contrast, mutations in genes that accumulate lipid-linked core oligosaccharides in which five or more mannose residues have been attached or that are defective in the later processing reactions, including ALG3 (7,14), ALG5 (7,15), ALG6 (7,16), ALG8 (17), ALG9 (18), and ALG10 (19), show little or no growth phenotype. Truncated oligosaccharides are transferred by OST to proteins in vivo (11,20) and in vitro (21)(22)(23), though the full-length, glucosylated Glc 3 Man 9 GlcNAc 2 is the preferred substrate (21,24). Although the transfer of truncated oligosac-charide structures is tolerated, mutations that block OST activity are lethal (25), demonstrating that N-linked glycosylation is an essential function.…”
mentioning
confidence: 99%